2016
DOI: 10.1155/2016/8607038
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity of Hippocampal Excitatory-Inhibitory Balance: Missing the Synaptic Control in the Epileptic Brain

Abstract: Synaptic plasticity is the capacity generated by experience to modify the neural function and, thereby, adapt our behaviour. Long-term plasticity of glutamatergic and GABAergic transmission occurs in a concerted manner, finely adjusting the excitatory-inhibitory (E/I) balance. Imbalances of E/I function are related to several neurological diseases including epilepsy. Several evidences have demonstrated that astrocytes are able to control the synaptic plasticity, with astrocytes being active partners in synapti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
83
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(86 citation statements)
references
References 168 publications
(206 reference statements)
2
83
0
1
Order By: Relevance
“…The balance between excitation and inhibition may be more critical to neural function and behaviour than either neural excitability or inhibition alone (Bonansco & Fuenzalida, 2016;Cash, Udupa, et al, 2017d;Meunier, Chameau, & Fossier, 2017;Turrigiano, 2011), and evidence suggests TBS may have an influence in this regulatory property in animal (Moreau, Amar, Callebert, & Fossier, 2013) and humans (Chung, Rogasch, Hoy, Sullivan, et al, 2018b;Hoy et al, 2016;Legon et al, 2016). Therefore, exploratory analyses were performed regarding the relationship between iTBS-induced change in P60 and N100 amplitudes in order to examine whether significant differences in any of the iTBS conditions could reflect altered inhibitory/excitatory balances (Noda, Zomorrodi, Cash, et al, 2017d).…”
Section: Tms-evoked Potentialsmentioning
confidence: 99%
“…The balance between excitation and inhibition may be more critical to neural function and behaviour than either neural excitability or inhibition alone (Bonansco & Fuenzalida, 2016;Cash, Udupa, et al, 2017d;Meunier, Chameau, & Fossier, 2017;Turrigiano, 2011), and evidence suggests TBS may have an influence in this regulatory property in animal (Moreau, Amar, Callebert, & Fossier, 2013) and humans (Chung, Rogasch, Hoy, Sullivan, et al, 2018b;Hoy et al, 2016;Legon et al, 2016). Therefore, exploratory analyses were performed regarding the relationship between iTBS-induced change in P60 and N100 amplitudes in order to examine whether significant differences in any of the iTBS conditions could reflect altered inhibitory/excitatory balances (Noda, Zomorrodi, Cash, et al, 2017d).…”
Section: Tms-evoked Potentialsmentioning
confidence: 99%
“…Epilepsy is a disorder characterized by recurrent spontaneous seizures due to excessive network activity. Among the multiple mechanisms that are proposed to induce seizures, the most accepted mechanism proposes that seizures are caused by the disruption of synaptic E/I balance, which promotes neuronal hyperexcitability and hypersynchronization, through either an increase in excitatory synaptic transmission or decrease in inhibitory synaptic transmission or both (Bonansco & Fuenzalida, ; Fritschy, ). In particular, it has been suggested that dysfunction of GABAergic signaling is critical for epileptogenesis (Cossart et al, ; Kobayashi & Buckmaster, ; Leroy, Poisbeau, Keller, & Nehlig, ).…”
Section: Introductionmentioning
confidence: 99%
“…transmission or decrease in inhibitory synaptic transmission or both (Bonansco & Fuenzalida, 2016;Fritschy, 2008). In particular, it has been suggested that dysfunction of GABAergic signaling is critical for epileptogenesis (Cossart et al, 2001;Kobayashi & Buckmaster, 2003;Leroy, Poisbeau, Keller, & Nehlig, 2004).…”
mentioning
confidence: 99%
“…Indeed, circuit models for diverse neuronal ensembles fail to recapitulate functional patterns unless these aspects are accounted for 1,2 . The misregulation of any one of these organizational parameters can result in neurodevelopmental disorders and intellectual disabilities like autism 3 , epilepsy 4 , and other synaptopathies 5 . Revealing the molecular mechanisms that ensure all of these facets are achieved is a critical step in understanding circuit assembly and function.…”
Section: Introductionmentioning
confidence: 99%